Importance of albumen during embryonic development in avian species, with emphasis on domestic chicken. Issue 3 (29th August 2014) - WILLEMS, E.; DECUYPERE, E.; BUYSE, J.; EVERAERT, N.
<x content-type="archive" xml:space="preserve">Abstract</x> Depending on the bird species, about 33-86% of the egg content consists of albumen. In eggs from domestic fowl, albumen contains about 10.5% protein and 88.5% of water and may be regarded as the main water source for the developing embryo. Besides carbohydrates, lipids, and inorganic ions, over 90% of the solids in the albumen are proteins. Several factors are known to influence the amount and composition of the albumen: egg weight, age and genetics of the parent flock, amount and quality of the feed provided, environmental factors (e.g. temperature, light), position in laying sequence, and also storage conditions of eggs prior to incubation. The albumen content of an egg plays an important role during embryonic development. Not only for formation of sub-embryonic fluid, but albumen proteins are known to flow into the amniotic cavity, the yolk sac and finally the digestive tract of the embryo and are used as the main source of proteins for tissue synthesis. Partial removal of albumen had negative consequences on chick weight at hatch, reduced the amount of amniotic and allantoic fluid and may reduce the water content of the chick and the residual yolk. Replacing the removed albumen with saline, however, reduced the residual yolk weight without differences in water content, suggesting increased uptake and utilisation of yolk, possibly as a compensation for the removed albumen proteins. In addition to reduced chick weight at hatch, some authors report an asymmetric growth restriction where nutrients are diverted away from non-vital organs in favour of brain and heart, with a relative 'sparing' of these latter two organs. Partial albumen removal led to a reduced whole-body protein synthesis, similar to eggs containing naturally less albumen. Importantly, several studies reported some long-term effects of albumen removal on growth, indicating that prenatal environment will have life-long consequences.